Sri Lanka: ClimBeR Inception Workshop Report - Jeya Raj, Renuka; Mascarenhas, M.; Amarnath, Giriraj; Amarasinghe, Upali A.; Alahacoon, Niranga; Singarachchi, Manahari (International Water Management Institute, 2023)
Climate variability and extreme weather events such as floods and droughts continue to increase due to climate change. These changes will have significant impacts on low- and middle-income countries. Without transformative climate adaptation solutions, millions of smallholder farmers will face severe losses because of increased climate variability. The CGIAR Initiative on Climate Resilience (‘ClimBeR’) was designed to develop bold transformative climate actions by delivering science and innovation to transform food, land, and water systems that will help smallholder farmers and local communities better adapt to the impacts of climate variability. ClimBeR aims to increase the adaptive capacity of countries by reducing risk for producers’ livelihoods and in value chains; understanding climate security risks and identifying paths to climate-resilient peace; ensuring policymakers have the necessary evidence to develop policies and adaptation strategies; building capacity with policies that bring together local needs and available tools to enable governance for resilience; scaling climate finance; and ensuring social equity. ClimBeR currently contributes towards increasing the adaptation capacity of six focal countries: Guatemala, Kenya, Morocco, the Philippines, Senegal and Zambia. ClimBeR’s work is now being also extended to Sri Lanka, with the support of Japan’s Ministry of Agriculture, Forestry and Fisheries (MAFF). The international Water management Institute (IWMI) will implement ClimBeR’s Governance for Resilience (G4R) work stream in Sri Lanka. This includes working closely with partners at the local, national and regional levels to tackle the vulnerability to climate change using multi-scale polycentric governance (MPG) and a transformative adaptation framework, and co-developing products and tools to facilitate early warning, early action and early finance (AWARE) and climate smart governance (CSG).